SH-SiGO / ADN / GAP-ETPE compound and preparation method thereof
By introducing SH-SiGO and ADN into GAP-ETPE, the SH-SiGO/ADN/GAP-ETPE complex was prepared, which solved the problem of insufficient performance of GAP-ETPE and significantly improved its explosion, combustion and safety performance.
Patent Information
- Application Number
- CN202411868961.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
AI Technical Summary
The existing GAP-ETPE has poor explosion, combustion and safety performance, high carbon content leads to poor explosion and combustion heat, and high impact sensitivity affects safety performance.
The SH-SiGO/ADN/GAP-ETPE complex was prepared by introducing thiol-functionalized graphene oxide (SH-SiGO) and ammonium dinitamide (ADN) into polyazid glycidyl ether-based energetic thermoplastic elastomer (GAP-ETPE), and its composition was changed to improve performance.
It improves the explosion and combustion heat of GAP-ETPE, reduces the impact sensitivity, thereby improving its explosion, combustion and safety performance.
Smart Images

Figure BDA0005195262730000021 
Figure BDA0005195262730000022 
Figure BDA0005195262730000023
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energetic materials, and specifically relates to a thiol-functionalized graphene oxide (SH-SiGO) / ammonium dinitramide (ADN) / polyazide glycidyl ether-based energetic thermoplastic elastomer (GAP-ETPE) composite, a preparation method and an application thereof. Background Art
[0002] Energetic thermoplastic elastomer (ETPE) as a solid propellant binder can give the propellant advantages such as high energy, insensitivity, low characteristic signal and recyclability. Azide-based energetic thermoplastic elastomers have the advantages of large heat release, no need for oxygen consumption during decomposition, and good compatibility with nitramine explosives, which have attracted widespread attention. Among them, polyazide glycidyl ether (GAP)-based ETPE is a representative. Solid propellants based on GAP-ETPE binders have become a research hotspot for thermoplastic elastomer propellants. However, due to the high carbon content of the GAP-ETPE chain, its explosion and combustion performance are poor, which affects the explosion and combustion performance of the GAP-ETPE binder formulation. In addition, GAP-ETPE contains more azide groups (-N3), which leads to its high impact sensitivity, affecting its safety performance. In the patent "A Method for Preparing Energetic Thermoplastic Elastomer Composites" (Authorization No.: ZL202010885177.X), Wang Yinglei et al. added thiol-functionalized graphene oxide to GAP-ETPE, and improved the thermal stability of the original GAP-ETPE and lowered the glass transition temperature of the original GAP-ETPE. However, the carbon content of thiol-functionalized graphene oxide is also high. After adding it, it cannot improve the explosive heat and combustion heat of GAP-ETPE. Summary of the invention
[0003] The invention provides a thiol-functionalized graphene oxide (SH-SiGO) / ammonium dinitramide (ADN) / glycidyl polyazide energetic thermoplastic elastomer (GAP-ETPE) composite, a preparation method and an application thereof. The composite is prepared by introducing SH-SiGO and ADN into GAP-ETPE. The explosion, combustion and safety performances of GAP-ETPE are improved by changing the addition amounts of SH-SiGO and ADN without changing the structure of GAP-ETPE.
[0004] In order to achieve the above technical tasks, the present invention adopts the following technical solutions:
[0005] A SH-SiGO / ADN / GAP-ETPE composite is prepared by a solvent volatilization method using mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazido glycidyl ether-based energetic thermoplastic elastomer; the average molecular weight of the polyazido glycidyl ether-based energetic thermoplastic elastomer is 20000-30000; and the mass ratio of mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazido glycidyl ether-based energetic thermoplastic elastomer is 1:(4-8):(90-190).
[0006] Optionally, the mass ratio of the mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:5:100.
[0007] Optionally, the molecular structure of the GAP-ETPE is as follows:
[0008]
[0009] Where 30≤a, b, c≤45, and a, b and c are all integers.
[0010] Optionally, the molecular structure of the SH-SiGO is as follows:
[0011]
[0012] Optionally, the molecular structure of the raw material ADN is as follows:
[0013]
[0014] The method for preparing any of the SH-SiGO / ADN / GAP-ETPE composites of the present invention comprises the following steps:
[0015] Step 1: SH-SiGO is dispersed and dissolved in tetrahydrofuran to obtain a SH-SiGO dispersion, wherein the amount ratio of SH-SiGO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g;
[0016] Step 2: GAP-ETPE is dissolved in tetrahydrofuran to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g;
[0017] Step 3: ADN is added to N-methylpyrrolidone to obtain an ADN solution, wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g;
[0018] Step 4: SH-SiGO dispersion and GAP-ETPE clear solution are mixed to obtain a mixed solution of SH-SiGO and GAP-ETPE;
[0019] Step 5: The ADN solution is dropped into the mixed solution of SH-SiGO and GAP-ETPE under stirring, and the mixture is evenly mixed, and the composite is obtained after standing and drying.
[0020] Optionally, the solutions prepared in steps 1-3 are stirred at a temperature range of 20 to 35° C. for 1 to 2 hours.
[0021] Optionally, in step 4, the mixed solution is stirred at 20-40° C. for 0.5-1 h.
[0022] Optionally, the dropping temperature in step 5 is 20-40° C., and after the dropping is completed, the system is stirred for 0.5-1 h, left to stand at room temperature for 1-2 weeks, and dried at 30-40° C. for 2-4 h to obtain the composite.
[0023] Application of any of the SH-SiGO / ADN / GAP-ETPE composites described in the present invention for preparing solid propellant adhesives.
[0024] Compared with the prior art, the present invention has the following beneficial technical effects:
[0025] The prepared SH-SiGO / ADN / GAP-ETPE composite of the present invention can increase the explosion heat and combustion heat of the original GAP-ETPE, the explosion heat is increased by 63.1 J / g to 470.2 J / g, the combustion heat is increased by 1060.0 J / g to 2155.7 J / g, and the impact sensitivity of GAP-ETPE can be reduced from 9 J to 51 J to 76 J. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0027] Figure 1 This is a SEM image of the raw material GAP-ETPE composite prepared in Example 1 of the present invention.
[0028] Figure 2 This is a SEM image of the SH-SiGO / ADN / GAP-ETPE composite prepared in Example 1 of the present invention.
[0029] Figure 3 This is the IR graph of the raw material GAP-ETPE composite prepared in Example 1 of the present invention;
[0030] Figure 4 This is the IR graph of the SH-SiGO / ADN / GAP-ETPE composite prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The following detailed description of the present invention is exemplary and does not limit the scope of the present invention. Based on the embodiments of the present invention, for ordinary technicians in the field, all uncreative improvements should be considered as the protection scope of the present invention without departing from the present invention.
[0032] The invention provides a thiol-functionalized graphene oxide (SH-SiGO) / ammonium dinitramide (ADN) / polyazide glycidyl ether-based energetic thermoplastic elastomer (GAP-ETPE) composite and a preparation method thereof, belonging to the technical field of energetic materials.
[0033] The molecular structure of SH-SiGO is shown below:
[0034]
[0035] The molecular structure of the raw material ADN is as follows:
[0036]
[0037] The molecular structure of the raw material GAP-ETPE is as follows:
[0038]
[0039] Wherein 30≤a, b, c≤45, and a, b and c are all integers; the average molecular weight of the polymer is 20000-30000; it is prepared according to the method disclosed in the literature "Preparation and Properties of GAP-ETPE / NC Blends", Energetic Materials, 24(4):331-335.
[0040] ADN (chemical name: ammonium dinitramide) is a new type of high-energy green oxidant composed of ammonium cations and dinitramide anions. It is one of the typical representatives of the third generation of energetic materials and has high density (1.82g / cm 3 ), high oxygen coefficient (2.0), low sensitivity, clean fuel gas (halogen-free), etc., representing the international advanced level of high-energy oxidants. Compared with the common oxidant ammonium perchlorate (AP), ADN has a higher formation enthalpy (ADN: -1208kJ / kg, AP: -2782kJ / kg), a smaller average relative molecular mass of fuel gas (ADN: 26, AP: 31), and the theoretical specific impulse of ADN-based solid propellants with the same mass content is 3s to 10s higher than that of AP-based solid propellants, representing the international advanced level of today's high-energy propellants. It can be added to GAP-ETPE together with thiol-functionalized graphene oxide to improve its explosion, combustion and safety performance.
[0041] The invention uses SH-SiGO, ADN and GAP-ETPE as raw materials and adopts a solvent volatilization method to prepare the composite material; the mass ratio of mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazide glycidyl ether energetic thermoplastic elastomer is 1:(4-8):(90-190); the composite material specifically comprises the following steps: adding SH-SiGO into tetrahydrofuran and ultrasonicating; adding GAP-ETPE into tetrahydrofuran and stirring; adding ADN into N-methylpyrrolidone and stirring; pouring SH-SiGO dispersion into a mixed solution of GAP-ETPE and tetrahydrofuran and stirring; dropping ADN solution into a mixed solution of SH-SiGO and GAP-ETPE, stirring evenly, and standing at room temperature for 1-2 weeks to obtain a mercaptofunctionalized graphene oxide / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite material. The prepared SH-SiGO / ADN / GAP-ETPE composite of the present invention can increase the explosion heat and combustion heat of the original GAP-ETPE, the explosion heat is increased by 63.1 J / g to 470.2 J / g, the combustion heat is increased by 1060.0 J / g to 2155.7 J / g, and the impact sensitivity of GAP-ETPE can be reduced from 9 J to 51 J to 76 J.
[0042] More specific steps include:
[0043] Step 1: SH-SiGO is dispersed and dissolved in tetrahydrofuran to obtain a SH-SiGO dispersion, wherein the amount ratio of SH-SiGO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g;
[0044] Step 2: GAP-ETPE is dissolved in tetrahydrofuran to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g;
[0045] Step 3: ADN is added to N-methylpyrrolidone to obtain an ADN solution, wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g;
[0046] Step 4: SH-SiGO dispersion and GAP-ETPE clear solution are mixed to obtain a mixed solution of SH-SiGO and GAP-ETPE;
[0047] Step 5: The ADN solution is dropped into the mixed solution of SH-SiGO and GAP-ETPE under stirring, and the mixture is evenly mixed, and the composite is obtained after standing and drying.
[0048] The SH-SiGO in step 1 adopts the preparation method of mercaptosilicon functionalized graphene oxide described in patent (application number 202010885150.0) to prepare mercaptosilicon functionalized graphene oxide, wherein the mercaptosilicon functionalized graphene oxide mainly prepared is 3-mercaptopropyltriethoxysilane modified graphene oxide;
[0049] More specific steps include:
[0050] Step 1, using the preparation method of mercaptosilicon functionalized graphene oxide described in patent (application number 202010885150.0) to prepare mercaptosilicon functionalized graphene oxide, wherein the mercaptosilicon functionalized graphene oxide mainly prepared is 3-mercaptopropyltriethoxysilane modified graphene oxide;
[0051] Step 2, adding SH-SiGO to tetrahydrofuran to obtain a SH-SiGO dispersion, and ultrasonically dispersing it at a temperature range of 20 to 35° C. for 1 to 2 hours, wherein the amount ratio of SH-SiGO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g;
[0052] Step 3, adding GAP-ETPE to tetrahydrofuran, stirring at a temperature range of 20 to 35° C. for 1 to 2 hours, filtering out insoluble matter therein to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g;
[0053] Step 4, adding ADN to N-methylpyrrolidone, stirring for 1 to 2 hours at a temperature range of 20 to 35° C., until ADN is completely dissolved, to obtain an ADN solution; wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g;
[0054] Step 5, pouring the SH-SiGO dispersion obtained in step 2 into the GAP-ETPE clear solution obtained in step 3, stirring the system at 20-40° C. for 0.5-1 h, and obtaining a mixed solution of SH-SiGO and GAP-ETPE after the solution is uniform;
[0055] Step 6, the ADN solution obtained in step 4 is added dropwise to the mixed solution of SH-SiGO and GAP-ETPE obtained in step 5 under stirring, wherein the dropping temperature is 20-40° C. After the dropping is completed, the system is stirred for 0.5-1 h. After stirring evenly, it is allowed to stand at room temperature for 1-2 weeks, and then dried at 30-40° C. for 2-4 h to obtain the corresponding thiol-functionalized graphene oxide (SH-SiGO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite.
[0056] As a two-dimensional carbon nanostructured material, graphene oxide has attracted much attention in the fields of nanocomposites, sensors, hydrogen storage capacitors and batteries. Thiol-functionalized graphene oxide has extremely high mechanical properties, good biocompatibility, superior electron transport capacity and excellent electrochemical properties, making it an ideal compound for improving the mechanical properties of materials.
[0057] Among the raw materials involved in the present invention, the graphene oxide raw material is purchased through the distributor Beijing Bailingwei Technology Co., Ltd. Ammonium dinitramide (ADN) is provided by the Xi'an Modern Chemistry Research Institute, and the impact sensitivity is 9J. Polyazide glycidyl ether (GAP), with a relative molecular weight of 3000, is a commercially available product of the Xi'an Modern Chemistry Research Institute. The polyazide glycidyl ether-based energetic thermoplastic elastomer GAP-ETPE in the raw materials of the present invention is prepared according to the method disclosed in the document "Preparation and Properties of GAP-ETPE / NC Blended Polymers", Energetic Materials, 24(4):331-335. The relative molecular weight of GAP-ETPE is 20000-30000, the explosion heat is 1826.6J / g, the combustion heat is 21758.9J / g, and the impact sensitivity is 9J.
[0058] Embodiment 1:
[0059] 60 mg SH-SiGO was added to 150 g tetrahydrofuran and ultrasonically dispersed at 25°C for 1.5 h. 6.0 g GAP-ETPE was added to 200 g tetrahydrofuran and stirred at 25°C for 1.5 h until GAP-ETPE was completely dissolved. 0.3 g ADN was added to 50 g N-methylpyrrolidone and stirred at 25°C for 1.5 h until ADN was completely dissolved. The SH-SiGO dispersion was poured into the GAP-ETPE mixed solution and the system was stirred at 30°C for 1 h until the solution was uniform. The N-methylpyrrolidone solution of ADN was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO under stirring at 30°C, stirred for 1 h after the addition, and then poured into the mold. After being placed at room temperature for 2 weeks, the corresponding thiol-functionalized graphene oxide (SH-SiGO) / ammonium dinitramide (ADN) / polyazide glycidyl ether energetic thermoplastic elastomer (GAP-ETPE) composite (6.0 g) was obtained by drying at 35 °C for 3 h. The explosion heat of the SH-SiGO / ADN / GAP-ETPE composite was 2296.8 J / g, which was 470.2 J / g higher than that of GAP-ETPE, the combustion heat was 23914.6 J / g, which was 2155.7 J / g higher than that of GAP-ETPE, and the impact sensitivity was 76 J, which was 67 J higher than that of GAP-ETPE.
[0060] Structural analysis
[0061] (1) Scanning electron microscopy (SEM) analysis
[0062] The surface morphology of GAP-ETPE and its composite was studied using a scanning electron microscope. Pure GAP-ETPE is relatively smooth, but when SH-SiGO and ADN are added, the GAP-ETPE composite becomes relatively rough, and ADN and SH-SiGO can be seen, while GAP-ETPE is coated on top. Figure 1 This is the SEM image of the raw material GAP-ETPE prepared in Example 1. Figure 2 This is the SEM image of the SH-SiGO / ADN / GAP-ETPE composite prepared in Example 1.
[0063] (2) Infrared analysis
[0064] Figure 3 This is the IR graph of the raw material GAP-ETPE prepared in Example 1. Figure 4 This is the IR graph of the SH-SiGO / ADN / GAP-ETPE composite prepared in Example 1. From the infrared graph, it can be seen that the SH-SiGO / ADN / GAP-ETPE composite has a wavelength of 3057 cm -1 (NH4 + ), 1623cm -1 (NO2) and 1283cm -1 (NO2) shows the characteristic peak of ADN. When the amount of SH-SiGO added is small, its characteristic peaks such as Si-O bond are not obvious in infrared, while other characteristic peaks such as hydroxyl, carbonyl, alkoxy and other functional groups are also found in GAP-ETPE.
[0065] Embodiment 2:
[0066] 13 mg SH-SiGO was added to 20 g tetrahydrofuran, ultrasonically dispersed at 20 ° C for 1.5 h, 1.6 g GAP-ETPE was added to 150 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.06 g ADN was added to 25 g N-methylpyrrolidone, stirred at 20 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 35 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 1 week, it was dried at 40 ° C for 2 h to obtain 4.2 g of the corresponding SH-SiGO / ADN / GAP-ETPE composite. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 1900.4J / g, the combustion heat is 22847.6J / g, and the impact sensitivity is 53J.
[0067] Embodiment 3:
[0068] 21 mg SH-SiGO was added to 20 g tetrahydrofuran, ultrasonically dispersed at 22 ° C for 1.5 h, 3.0 g GAP-ETPE was added to 160 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.09 g ADN was added to 15 g N-methylpyrrolidone, stirred at 20 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 30 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 40 ° C for 2 h to obtain 4.7 g of the corresponding SH-SiGO / ADN / GAP-ETPE composite. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 1947.2 J / g, the combustion heat is 23018.6 J / g, and the impact sensitivity is 56 J.
[0069] Embodiment 4:
[0070] 27 mg SH-SiGO was added to 40 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 1 h, 5.1 g GAP-ETPE was added to 120 g tetrahydrofuran, stirred at 24 ° C for 1.5 h, and GAP-ETPE was completely dissolved; 0.15 g ADN was added to 30 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 30 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 30 ° C, stirred for 1 h after dropping, and poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 30 ° C for 3 h to obtain the corresponding SH-SiGO / ADN / GAP-ETPE composite 5.0 g. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 1995.8J / g, the combustion heat is 22976.1J / g, and the impact sensitivity is 65J.
[0071] Embodiment 5:
[0072] 35 mg SH-SiGO was added to 80 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 1.5 h, 5.3 g GAP-ETPE was added to 150 g tetrahydrofuran, stirred at 20 ° C for 1.5 h, and GAP-ETPE was completely dissolved; 0.19 g ADN was added to 40 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 35 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 20 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 35 ° C for 2 h to obtain the corresponding SH-SiGO / ADN / GAP-ETPE composite 5.3 g. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 2174.8 J / g, the combustion heat is 23618.7 J / g, and the impact sensitivity is 54 J.
[0073] Embodiment 6:
[0074] 43 mg SH-SiGO was added to 110 g tetrahydrofuran, ultrasonically dispersed at 25 ° C for 2 h, 5.6 g GAP-ETPE was added to 180 g tetrahydrofuran, stirred at 20 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.22 g ADN was added to 35 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 30 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 1 week, it was dried at 30 ° C for 4 h to obtain the corresponding SH-SiGO / ADN / GAP-ETPE composite 5.5 g. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 2207.5J / g, the combustion heat is 23101.8J / g, and the impact sensitivity is 60J.
[0075] Embodiment 7:
[0076] 49 mg SH-SiGO was added to 130 g tetrahydrofuran, ultrasonically dispersed at 32 ° C for 1 h, 5.7 g GAP-ETPE was added to 160 g tetrahydrofuran, stirred at 22 ° C for 1.5 h, until GAP-ETPE was completely dissolved; 0.27 g ADN was added to 40 g N-methylpyrrolidone, stirred at 25 ° C for 1 h, until ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 24 ° C for 0.5 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 35 ° C, stirred for 0.5 h after dropping, and poured into the mold. After being placed at room temperature for 1 week, it was dried at 30 ° C for 3 h to obtain the corresponding SH-SiGO / ADN / GAP-ETPE composite 5.6 g. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 2288.1J / g, the combustion heat is 22886.1J / g, and the impact sensitivity is 54J.
[0077] Embodiment 8:
[0078] 53 mg SH-SiGO was added to 110 g tetrahydrofuran, ultrasonically dispersed at 27 ° C for 1 h, 4.8 g GAP-ETPE was added to 170 g tetrahydrofuran, stirred at 26 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.29 g ADN was added to 35 g N-methylpyrrolidone, stirred at 20 ° C for 1 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 33 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 36 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, the corresponding SH-SiGO / ADN / GAP-ETPE composite 4.7 g was obtained by drying at 34 ° C for 2 h. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 1994.7J / g, the combustion heat is 22991.8J / g, and the impact sensitivity is 54J.
[0079] Embodiment 9:
[0080] 33 mg SH-SiGO was added to 100 g tetrahydrofuran and ultrasonically dispersed at 27 ° C for 2 h. 5.9 g GAP-ETPE was added to 160 g tetrahydrofuran and stirred at 24 ° C for 1 h until GAP-ETPE was completely dissolved. 0.17 g ADN was added to 40 g N-methylpyrrolidone and stirred at 20 ° C for 2 h until ADN was completely dissolved. SH-SiGO dispersion was poured into the GAP-ETPE mixed solution and the system was stirred at 36 ° C for 1 h until the solution was uniform. The N-methylpyrrolidone solution of ADN was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 30 ° C, stirred for 1 h after addition, and then poured into the mold. After being placed at room temperature for 2 weeks, the corresponding SH-SiGO / ADN / GAP-ETPE composite 4.8 g was obtained by drying at 30 ° C for 3 h. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 2166.5J / g, the combustion heat is 23417.8J / g, and the impact sensitivity is 71J.
[0081] Embodiment 10:
[0082] 27 mg SH-SiGO was added to 80 g tetrahydrofuran, ultrasonically dispersed at 30 ° C for 1.5 h, 4.3 g GAP-ETPE was added to 120 g tetrahydrofuran, stirred at 25 ° C for 1 h, and GAP-ETPE was completely dissolved; 0.20 g ADN was added to 30 g N-methylpyrrolidone, stirred at 25 ° C for 2 h, and ADN was completely dissolved; SH-SiGO dispersion was poured into the GAP-ETPE mixed solution, and the system was stirred at 25 ° C for 1 h until the solution was uniform; ADN N-methylpyrrolidone solution was added dropwise to the mixed solution of GAP-ETPE and SH-SiGO at 25 ° C, stirred for 1 h after dropping, and then poured into the mold. After being placed at room temperature for 2 weeks, it was dried at 30 ° C for 2 h to obtain 4.2 g of the corresponding SH-SiGO / ADN / GAP-ETPE composite. The explosion heat of SH-SiGO / ADN / GAP-ETPE composite is 2033.4 J / g, the combustion heat is 23547.1 J / g, and the impact sensitivity is 58 J.
[0083] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A SH-SiGO / ADN / GAP-ETPE composite, characterized in that: The composite is prepared by a solvent volatilization method using mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer; The average molecular weight of the polyazide glycidyl ether-based energetic thermoplastic elastomer is 20,000 to 30,000; The mass ratio of mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:(4-8):(90-190).
2. The SH-SiGO / ADN / GAP-ETPE composite according to claim 1, characterized in that: The mass ratio of the mercaptosilicon functionalized graphene oxide, ammonium dinitramide and polyazide glycidyl ether-based energetic thermoplastic elastomer is 1:5:
100.
3. The SH-SiGO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of the GAP-ETPE is shown below: Where 30≤a, b, c≤45, and a, b and c are all integers.
4. The SH-SiGO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of SH-SiGO is as follows:
5. The SH-SiGO / ADN / GAP-ETPE composite according to claim 1 or 2, characterized in that: The molecular structure of the raw material ADN is as follows:
6. The method for preparing the SH-SiGO / ADN / GAP-ETPE composite according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: SH-SiGO is dispersed and dissolved in tetrahydrofuran to obtain a SH-SiGO dispersion, wherein the amount ratio of SH-SiGO to tetrahydrofuran is 10 mg to 60 mg: 20 g to 150 g; Step 2: GAP-ETPE is dissolved in tetrahydrofuran to obtain a GAP-ETPE clear solution, wherein the amount ratio of GAP-ETPE to tetrahydrofuran is 4.0 g to 6.0 g: 100 g to 200 g; Step 3: ADN is added to N-methylpyrrolidone to obtain an ADN solution, wherein the amount ratio of ADN to N-methylpyrrolidone is 0.06 g to 0.3 g: 10 g to 50 g; Step 4: SH-SiGO dispersion and GAP-ETPE clear solution are mixed to obtain a mixed solution of SH-SiGO and GAP-ETPE; Step 5: The ADN solution is dropped into the mixed solution of SH-SiGO and GAP-ETPE under stirring, and the mixture is evenly mixed, and the composite is obtained after standing and drying.
7. The method for preparing the SH-SiGO / ADN / GAP-ETPE composite according to claim 6, characterized in that: The solutions prepared in steps 1-3 are all stirred at a temperature range of 20 to 35° C. for 1 to 2 hours.
8. The method for preparing the SH-SiGO / ADN / GAP-ETPE composite according to claim 6, characterized in that: In the step 4, the mixed solution is stirred at 20-40° C. for 0.5-1 h.
9. The method for preparing the SH-SiGO / ADN / GAP-ETPE composite according to claim 6, characterized in that: The dropping temperature in step 5 is 20-40° C. After the dropping is completed, the system is stirred for 0.5-1 h, left to stand at room temperature for 1-2 weeks, and dried at 30-40° C. for 2-4 h to obtain the composite.
10. Use of the SH-SiGO / ADN / GAP-ETPE composite according to any one of claims 1 to 5 for preparing a solid propellant adhesive.
Citation Information
Patent Citations
A method for preparing an energetic thermoplastic elastomer composite
CN112047793B
Synthesis method of 3-mercaptopropyltriethoxysilane modified graphene oxide
CN112062784A